A transposição peritônio-aponeurótica bilateral no tratamento de hérnias ventrais na criança - Bernardo Almeida Campos (2008)
Ventral hernias in children can be caused either by congenital anomalies (omphaloceles and gastroschisis) or by previous laparotomies (incisional hernias). There are few published studies about the treatment of ventral hernias in children. The Bilateral Peritoneum-Aponeurotic Transposition (BPAT) technique described byLázaro da Silva (1971) has become an effective and safe approach for incisional hernias in adults. At the Section of Pediatric Surgery of the Hospital das Clínicas, Federal University of Minas Gerais, the BPAT was first applied in a child with incisional hernia. Thereafter it has also been used in children with epithelized omphaloceles. There was no previous published study concerning the treatment of incisional hernias in children, neither about the use of BPAT in the treatment of ventral hernias caused by omphaloceles or gastroschisis. Long-term results of BPATin children are unknown. The aim of this study was to evaluate early and late results of BPAT in children, especially the recurrence rate. This was a descriptive study of 22 children (14 female and eight male), aging from three months to nine years (meanage: 3 + 2,3 years), operated on by BPAT between 1978 and 2005. Six hernias were incisional and other 16 were caused by abdominal wall defects. Mean duration of the BPAT was 156 + 58 minutes. There were no intra-operative complications. Meanlength of postoperative stay was 8 + 10 days. Atelectasis was the most common and serious postoperative complication. Six (27,3%) children presented atelectasis. Three of them needed mechanical ventilation, two developed pneumonias and one died. There was only one (4,5%) early death in this series. Other respiratory complications were pneumonias (9%), bronchospasm (4,5%) and otitis (4,5%). Wound complications were also common, but with no severity. Seven (31,8%) childrenpresented minor wound complications in the early postoperative period, including four (18,1%) seromas, two (9%) infections and one (4,5%) bleeding. Long term follow-up was accomplished in 18 (81,8%) children, ranging from one year to 22 years (mean: 7,6 + 5,9 years). There were no serious complications late after the BPAT. Inguinal hernias ocurred in five (27,7%) children, another three (16,6%) complained of a poor cosmethic result and two (11,1%) presented with wound granulomas. The BPATavoided the use of prostethic meshes and their potential complications. There were no cases of abdominal compartment syndrome, bowel obstruction or enterocutaneous fistula in this series, neither technique related deaths. One girl died of meningitis late after the BPAT. Four (22,2%) children were successfully submitted to late laparotomies for other reasons. There was no recurrence in children operated on by the BPAT. The BPAT is an effective and safe option in children with ventralhernias secondary to abdominal wall defects and previous laparotomies.